MAQASID AL-SHARI’AH AND CORPORATE GOVERNANCE IN ISLAMIC FINANCE: INTEGRATING ESG PRINCIPLES FOR SUSTAINABLE DEVELOPMENT - Monira , Nurjahan Akter; Arup , Arnob Debnath; Rainak , Maisha (International Journal of Shari’ah and Corporate Governance Research, 2024)
Islamic finance has expanded alongside the growing prominence of Environmental, Social, and Governance (ESG) frameworks, yet the integration between Shariah-based objectives and ESG standards remains uneven and conceptually fragmented. While both systems emphasize ethics, social welfare, and sustainability, there is limited consolidated evidence explaining how Maqasid al-Shari’ah and Islamic corporate governance mechanisms practically align with ESG performance in Islamic financial institutions.The purpose of this study is to examine the convergence between Maqasid al-Shari’ah, Islamic corporate governance, and ESG frameworks, with a focus on how governance structures translate ethical objectives into measurable sustainability outcomes. This study employs a structured literature review and content analysis of peer-reviewed journal articles, policy reports, and empirical studies published between 2010 and 2024. A final sample of 72 academic studies was analyzed, covering Islamic banking, Shariah governance, ESG disclosure, and sustainable finance instruments. Descriptive statistics and thematic mapping were used to align ESG dimensions with Maqasid objectives and governance attributes. The results show that more than 80 percent of the reviewed studies report a strong conceptual alignment between ESG principles and Maqasid al-Shari’ah. Empirical studies indicate that Islamic banks with stronger Shariah governance frameworks demonstrate higher ESG scores, with social and governance dimensions improving by approximately 10–25 percent compared to peers with weaker Shariah oversight. Environmental performance shows a comparatively lower but positive association. The major findings suggest that Maqasid al-Shari’ah provides a coherent ethical foundation for ESG integration, and that effective Islamic corporate governance plays a measurable role in enhancing ESG outcomes within Islamic financial institutions. JEL Classification Codes: G21, G34, Q56, M14, O13.